PROFESSIONAL VALORIZATION AND HEALTH ACTIONS IN THE MILITARY POLICE OF TOCANTINS: AN EVOLUTIONARY ANALYSIS THROUGH FUNDAÇÃO PRÓ-TOCANTINS (Editora Impacto Científico, 2025)
The study analyzes how the Fundação Pró-Tocantins (FPTO) has contributed to the professional valorization and comprehensive health promotion of the Military Police officers of Tocantins. The general objective is to analyze the evolution of health services and benefits provided by the FPTO to Tocantins military in the period from 2020 to 2025. The research methodology adopts a quantitative and qualitative approach, combining bibliographical research and documentary analysis, integrating statistical data and content discussion to understand the evolution of services such as medical, dental, and psychological care, as well as wellness programs. The results reveal significant progress, especially after the inauguration of the new headquarters and the expansion of healthcare coverage to the state’s interior. Nevertheless, challenges remain concerning the strengthening of mental health initiatives, equitable distribution of professionals, and the updating of financial benefits. The decision of the Supreme Federal Court (ADI 5.368/TO), which made contributions to the FPTO optional, led to a temporary decrease in the number of beneficiaries, followed by stabilization and sustained institutional trust. It is concluded that the FPTO constitutes a strategic instrument for professional valorization and quality-of-life promotion, consolidating itself as an essential policy of care and support for the Tocantins military community.DOI: https://doi.org/10.56238/edimpacto2025.090-020